Types of phone usage: Age differences between younger and older persons - Simona-Nicoleta Vulpe; Corina Ilinca (Journal of Comparative Research in Anthropology and Sociology, 2017)
I Even if more and more people use mobile phones, the gap between younger and older age groups persists and its importance is timely and widened given the present ageing and digital inequality phenomena. How wide is the difference on types of phone usage between different age groups? For answering this research question, we employ binary logistic regressions on several types of phone usage keeping into account age and controlling for region, education, income and whether respondents use a feature phone or a smartphone. The analysed data come from the Spring Change Assessment Survey 2010 provided by the Pew Research Center and it is representative for the United States of America. Our results show that, net of the all the variables included in the model, older persons are less likely than younger persons to use such phone functions, but the strength of association is low. Education and income are relevant for these functions. Using a smartphone in comparison with using a feature phone is important in all the situations included, as well as income. Considering models only for older persons, over 65 years of age, college and income are less relevant. Using a smartphone is more likely than using a feature phone to encourage all types of phone usage, independently of age.